Preliminary treatment results of proton beam therapy with chemoradiotherapy for stage I–III esophageal cancer. (24th January 2016) - Takada, Akinori; Nakamura, Tatsuya; Takayama, Kanako; Makita, Chiyoko; Suzuki, Motohisa; Azami, Yusuke; Kato, Takahiro; Tsukiyama, Iwao; Hareyama, Masato; Kikuchi, Yasuhiro; Daimon, Takashi; Toyomasu, Yutaka; et al.
Abstract : Proton beam therapy might have the potential to reduce the risk of cardiac damage and might become one of the primary methods of esophageal cancer treatment. Abstract: The effect of proton beam therapy (PBT) on various cancers is controversial. We aimed to evaluate the efficacy and safety of PBT with alternating chemoradiotherapy (ACRT) for patients with stage I–III esophageal cancer. Two cycles of systemic chemotherapy with a continuous infusion of 5‐fluorouracil (5‐FU) on days 1–5 and a 5h infusion of nedaplatin (NDP) on day 6 were accompanied by thoracic irradiation using X‐ray therapy and PBT. During the first half of the treatment, X‐rays were delivered to the prophylactic area. During the second half of the treatment, proton beams were used to irradiate the involved field. To reduce the dose of cardiac irradiation, proton beams were delivered with posterior and posterior oblique angles. Between January 2009 and December 2012, 47 patients were enrolled in this study. The median follow‐up duration was 29 months for all patients and 40 months for survivors. The 3 year overall survival rate, progression‐free survival rate, and local control rate were 59.2%, 56.3%, and 69.8%, respectively. With respect to grade 3–4 late toxicities, there were no pleural or pericardial effusions, but two patients (4.3%) had esophageal stenosis, one patient (2.1%) had fistula, and two patients (4.3%) developed radiation pneumonitis. PBT with ACRT might have the potential to reduce the risk of cardiac damage and might become one of the primary methods of esophageal cancer treatment.